Relationship of opioid receptors with GABAergic neurons in the rat inferior colliculus - W. Tongjaroenbuangam (2018)
The inferior colliculus is a critical structure for processing auditory information and receives ascending and descending synaptic auditory projections. In addition to GABAergic and glutamatergic innervations, other neurotransmitter systems are also reported in the inferior colliculus, including opioid peptides. In the present study, the relative distribution of each type of opioid receptor, mu (MOR), delta (DOR) and kappa (KOR) within GABAergic neurons in the inferior colliculus was examined. GABA immunoreactivity was expressed by small, medium and large neurons and distributed in the central nucleus and the pericentral nucleus of the inferior colliculus. Immunostaining for MOR, DOR and KOR receptors was found in both disc-shaped cells and stellate cells. Punctiform β-endorphin immunolabelling was observed in the proximity of GABA-positive neurons. Co-localization of GABA and MOR receptors was observed in neurons and nerve terminals in the central nucleus, dorsal cortex and external cortex of the inferior colliculus. Quantification of the co-localization patterns determined that a higher proportion of GABA neurons was associated with MOR receptors compared with KOR or DOR receptors. © The Authors (2006).